Feasibility Assessment of Bioethanol Production in Arid Regions using Date Palm Feedstock - Hossein Yousefi; Sanaz Tabasi; Ali Mohammadi (Environmental Energy and Economic Research, 2023)
Climate change and the need to manage diminishing fossil fuel reserves are two of the biggest challenges facing the planet. It is widely accepted that we must now reduce the fossil energy consumption and increase the renewable energies production substantially. To achieve these targets, fossil fuels should be replaced by the renewable energies. One of the important renewable energies is biomass that gradually has become more popular for its production technology in recent years. This study focuses on the innovative production of bio-ethanol as a clean and efficient fuel. In this study, the date crop, which is found in arid regions including Iran, was selected as the raw material for bioethanol production. It was shown that Iran has a high potential of producing date crops and it is, unfortunately, going to be wasted yearly. Therefore, date crops are introduced as a new feedstock to produce bio-ethanol in Iran. Hence, feasibility and economic evaluation of this ingenious method are analyzed. According to 2014 statistics, the amount of bio-ethanol production from date crops calculated, 352873.91 tons in Iran. Then, the best region for this production identified based on the amount of date produced, annually. Following that, the profitability of this project is shown through NPV calculation that obtained 203 $M. Therefore, the payback period is considered as less than one year which proves that the idea of using date crops for ethanol production is highly economical in Iran.